Administrative data linkage in Canada: Implications for sociological research. (1st March 2022) - Yoshida, Yoko; Haan, Michael; Schaffer, Scott
Abstract: This paper explores some of the implications that administrative data, defined as data initially collected for purposes other than research, will have for Sociology. Although administrative data are "found" rather than "made" and, in turn, pose several challenges, we argue that the potential of these data warrant the investment, and may lead to a new methodological imagination that can shed a light on time‐tested concepts and advance our understanding of society. We show that it is already possible to advance several sociological debates through the use of administrative data and demonstrate the potential of these data through some examples drawn from classical sociological theory. We conclude by arguing that administrative data's potential will likely ensure that it becomes an important component of sociological research agendas in the coming years. RÉSUMÉ: Cet article explore certaines des implications que les données administratives—définies comme des données initialement collectées à des fins autres que la recherche—auront pour la sociologie. Quoique les données administratives soient « trouvées » plutôt que « faites » et, à leur tour, posent plusieurs défis, nous soutenons que le potentiel de ces données justifie l'investissement et peut conduire à une nouvelle imagination méthodologique, une qui peut mettre en lumière des concepts durables sociologiques et avancer notre compréhension de la société. Nous montrons qu'il est déjà possible de faire avancer plusieurs débats sociologiques avec lutilisation de données administratives, et nous démontrons le potentiel de ces données à travers quelques exemples tirés de la théorie sociologique classique. Nous concluons en affirmant que le potentiel des données administratives garantira probablement qu'elles deviendront une composante importante des recherches sociologiques à venir.